KONSTRUKSI SOSIAL MAKNA SELAMATAN DALAM KEHIDUPAN MASYARAKAT DESA KARETAN BANYUWANGI - Eka Mariska Putri Imra (Journal SOSIOLOGI, 2024)
This study aims to explore the social construction that shapes the meaning of selamatan in the lives of the people of Karetan Village, Banyuwangi, a tradition that combines religious and social aspects. Selamatan in this village is not only considered a religious ritual, but also a social process that creates and strengthens bonds between individuals in the community. The meaning of selamatan in Karetan Village is influenced by social dynamics, economic changes, and interactions between generations. This research uses a qualitative approach, the theoretical perspective used is social construction theory developed by Peter Ludwig Berger. In-depth interviews and collective observation are used to understand how people interpret and live selamatan in their daily lives. The main focus of the research is how selamatan functions as a mechanism for social identity formation and social network strengthening in the midst of rapid change. The findings of this study show that despite efforts to maintain traditions, selamatan undergoes changes in meaning along with the influence of modernization, where social and pragmatic aspects increasingly dominate. This research provides insight into the cultural dynamics in villages that are often overlooked in social studies, as well as how cultural practices remain relevant despite the pressures of modernization.